TC-PSLAP: Temporal Credential-Based Provably Secure and Lightweight Authentication Protocol for IoT-Enabled Drone Environments. (18th December 2021) - Ali, Zeeshan; Alzahrani, Bander A.; Barnawi, Ahmed; Al-Barakati, Abdullah; Vijayakumar, Pandi; Chaudhry, Shehzad Ashraf
Abstract : In smart cities, common infrastructures are merged and integrated with various components of information communication and technology (ICT) to be coordinated and controlled. Drones (unmanned aerial vehicles) are amongst those components, and when coordinated with each other and with the environment, the drones form an Internet of Drones (IoD). The IoD provides real-time data to the users in smart cities by utilizing traditional cellular networks. However, the delicate data gathered by drones are subject to many security threats and give rise to numerous privacy and security issues. A robust and secure authentication scheme is required to allow drones and users to authenticate and establish a session key. In this article, we proposed a provably secure symmetric-key and temporal credential-based lightweight authentication protocol (TC-PSLAP) to secure the drone communication. We prove that the proposed scheme is provably secure formally through the automated verification tool AVISPA and Burrows–Abadi–Needham logic (BAN logic). Informal security analysis is also performed to depict that the proposed TC-PSLAP can resist known attacks.